Reconstruction of the superior capsule of the shoulder joint in massive ruptures of the rotator cuff tendons (literature review) - E. N. Slaykovskiy; I. A. Kuklin; D. V. Menshova (Acta Biomedica Scientifica)
The prevalence of rotator cuff ruptures among injuries of the musculoskeletal system according to the literature is 20 %. Massive injuries to the rotator cuff of the shoulder are tears with  retraction of  more than 5  cm or  damage to  two or  more tendons. With massive injuries, the head of the humerus is decentrated, the biomechanics of the joint is impaired and, as a result, the progression of osteoarthritis occurs.The aim. To analyze the literature data of foreign and domestic authors and to provide an overview of modern views on the surgical treatment of massive ruptures of the rotator cuff tendons.Materials and methods. A search and analysis of the literature of foreign and domestic authors was  carried out using the  Internet resources PubMed, eLibrary in the period from 2010 to 2024.Results and discussion. To date, in treatment of massive ruptures, much attention is paid to the reconstruction of the upper capsule of the shoulder joint. The biomechanical principle underlying the  reconstruction of  the  superior capsule involves the use of a graft to close a tendon defect. Today, the most commonly used grafts are allografts, autografts, xenografts, and synthetic materials. This review presents surgical techniques and results of surgical treatment using the broad fascia of the thigh, dermal allografts, peroneus longus tendon, biceps brachii longus tendon, and Achilles tendon, but there is no consensus on the choice of grafts and methods of their fixation.Conclusion. An  analysis of  literature sources does not  provide a  clear answer to the question of choosing the most effective method of treating this pathology. The number of modern publications shows that the problem of improving the treatment of such patients is currently relevant and requires in-depth research.